Development of Evernoted Learning Media Center as Learning Innovation and Assistive Technology for People with Disabilities - Novariyanto, Rizki Agung; Utami, Prihma Sinta; Bashofi, Ferdinan; Rahadian, Septa; Setiani, Puspita Pebri; Firdausi, Faizah Ulumi; Sunuyeko, Nurcholis (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The development of Evernoted Learning Media Center aims to introduce inclusive learning innovations for people with disabilities. This study presents the design and implementation of an Evernoted-based learning platform with accessibility features. Employing the Research and Development (R&D) method, a need analysis was initially conducted through interviews with teachers and principals at three Special Needs Schools (SLB/Sekolah Luar Biasa) in Malang City. The analysis results were used to design an appropriate Evernoted Learning Media Center design. The platform incorporates accessibility features, including alternative text, contrast settings, and layer readers. Findings revealed that Evernoted could be configured into an effective learning medium, offering flexibility, personalization, and ease of users access with various types of disabilities, especially deaf people. The analysis results demonstrated that Evernoted Learning Media Center could be an effective alternative for meeting the varied learning needs of students with disabilities, particularly deaf people, through two versions: an augmented reality (AR)-based Android application and a virtual tour-based website. Validation results indicated the platform’s feasibility at 83.17%, categorizing it as very feasible to be tested on students with disabilities.